Penggunaan Strategi Pembelajaran Numbered Head Together (NHT) dalam Meningkatkan Minat Belajar Siswa pada Mapel Matematika Sub Materi Garis dan Sudut di Kelas VII A SMP Negeri 2 Arut Selatan Tahun Ajaran 2019/2020: The Use of Numbered Head Together (NHT) Learning Strategies to Increase Students' Learning Interest in the Math Mathematics, Line and Angle Materials in Class VII A SMP Negeri 2 Arut Selatan Academic Year 2019/2020 - Saragih, Rasmawati (Anterior Jurnal, 2022)
One of the subjects or subjects of mathematics at the junior high school level is about lines and angles; lines and angles are the material taught in Class VII A of SMP Negeri 2 Arut Selatan. Based on the 2019/2020 academic year test report, the mastery of mathematics material at SMP Negeri 2 Arut Selatan, related to the line and angle material, is 56.90%. This shows that students' learning interest in the material does not determine the lines and angles still. Therefore, the mathematics teacher, who also acts as a researcher to change the learning methods or strategies that are usually applied, namely applying the Numbered Head Together learning method or strategy (NHT). This Classroom Action Research (CAR) was conducted in Class VII A of SMP Negeri 2 Arut Selatan with 30 students. The reflection in the first cycle is that although students in learning mathematics still face some difficulties, the Lines and Angles sub-material, the NHT learning strategy in the first cycle will be implemented quite well. This can be seen in the enthusiasm shown by students in participating in learning and mastery of the material. Using the NHT learning strategy, the line and angle sub-material learning mathematics can be conducive. Applying the NHT learning strategy based on the Cooperative Learning learning strategy demands a lot of students' active roles both in group work and individually. This is evidenced by the acquisition of student learning outcomes that have increased from the pre-cycle to the second cycle.